Design of a biomimetic, small-scale artificial leaf surface for the study of environmental interactions - Huth, Miriam Anna; Huth, Axel; Schreiber, Lukas; Koch, Kerstin (Beilstein Journal of Nanotechnology, 2022)
The cuticle with its superimposed epicuticular waxes represents the barrier of all aboveground parts of higher plant primary tissues. Epicuticular waxes have multiple effects on the interaction of plants with their living and non-living environment, whereby their shape, dimension, arrangement, and chemical composition play significant roles. Here, the ability of self-assembly of wax after isolation from the leaves was used to develop a small-scale wax-coated artificial leaf surface with the chemical composition and wettability of wheat (Triticum aestivum) leaves. By thermal evaporation of extracted plant waxes and adjustment of the evaporated wax amounts, the wettability and chemical character of the microstructure of the surface of wheat leaves were transferred onto a technical surface. For the use of these artificial leaves as a test system for biotic (e.g., germination of fungal pathogens) and non-biotic (e.g., applied surfactants) interactions on natural leaf surfaces, the chemical composition and the wetting behavior should be the same in both. Therefore, the morphology, chemistry, and wetting properties of natural and artificial surfaces with recrystallized wax structures were analyzed by scanning electron microscopy, gas chromatography–mass spectrometry, and by the determination of water contact angles, contact angle hysteresis, and tilting angles. Wheat leaves of different ages were covered exclusively with wax platelets. The extracted wheat wax was composed of alcohols, aldehydes, esters, and acids. The main component was 1-octacosanol. The waxes recrystallized as three-dimensional structures on the artificial surfaces. The three tested wetting parameters resembled the ones of the natural surface, providing an artificial surface with the chemical information of epicuticular waxes and the wetting properties of a natural leaf surface.
Keywords: recrystallization; surface properties; wax composition; wetting; wheat